Synergistic activity between statins and bisphosphonates against acute experimental toxoplasmosis - Li, Zhu-Hong (2017)
Bisphosphonates are widely used for the treatment of bone disorders. These drugs also inhibit the growth of a variety of protozoan parasites, such as Toxoplasma gondii, the etiologic agent of toxoplasmosis. The target of the most potent bisphosphonates is the isoprenoid biosynthesis pathway enzyme farnesyl diphosphate synthase (FPPS). Based on our previous work on the inhibitory effect of sulfur-containing linear bisphosphonates against T. gondii, we investigated the potential synergistic interaction between one of these derivatives, 1-[(n-heptylthio)ethyl]-1,1-bisphosphonate (C7S), and statins, which are potent inhibitors of the host 3-hydroxy-3-methyl glutaryl-coenzyme A reductase (3-HMG-CoA reductase). C7S showed high activity against the T. gondii bifunctional farnesyl diphosphate (FPP)/geranylgeranyl diphosphate (GGPP) synthase (TgFPPS), which catalyzes the formation of FPP and GGPP (50% inhibitory concentration [IC50] = 31 ± 0.01 nM [mean ± standard deviation]), and modest effect against the human FPPS (IC50 = 1.3 ± 0.5 μM). We tested combinations of C7S with statins against the in vitro replication of T. gondii. We also treated mice infected with a lethal dose of T. gondii with similar combinations. We found strong synergistic activities when using low doses of C7S, which were stronger in vivo than when tested in vitro. We also investigated the synergism of several commercially available bisphosphonates with statins both in vitro and in vivo. Our results provide evidence that it is possible to develop drug combinations that act synergistically by inhibiting host and parasite enzymes in vitro and in vivo.